EFFECTIVENESS OF USING INTERACTIVE DIGITAL MEDIA INIMPROVING FISIOTHERAPY STUDENTS’ IN SPEAKING SKILLS ATMUHAMMADIYAH PRINGSEWU UNIVERSITY - Fini Widya Fransiska (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the effectiveness of using interactive digital media in improving the speaking skills of physiotherapy students at Muhammadiyah University Pringsewu. Speaking skills are an important competency for physiotherapy students, especially in therapeutic communication, patient education, and collaboration with other medical professionals. The research method used is quantitative with a quasi-experimental design using pre-test and post-test. The instruments used include a speaking skills test based on an assessment rubric and a student satisfaction questionnaire. The results of the data analysis show a significant increase in post-test scores compared to pre- test scores, as well as a high level of student satisfaction with the interactive digital media used. In conclusion, interactive digital media has proven effective in improving the professional communication quality of physiotherapy students and is recommended for integration into clinical practice-based learning.